Estimating, and setting targets for, the resilience of transport infrastructure. Issue 4 (30th July 2021) - Adey, Bryan T; Martani, Claudio; Kielhauser, Clemens; Robles, Ignacio Urqulijo; Papathanasiou, Natalia; Burkhalter, Marcel; Beltran-Hernando, Iñaki; Garcia-Sanchez, David
Abstract : To ensure that transport infrastructure provides acceptable levels of service with respect to extreme events, the resilience of the infrastructure needs to be estimated and targets for it need to be set. In this paper, the methodology proposed in the Foresee EU research project is presented. The methodology allows managers to measure, and set targets for, the resilience of transport systems in all situations. It requires clear definition of the transport system and how the service provided and the resilience are to be measured. The methodology allows consideration of the fact that transport infrastructure managers need to estimate resilience with various degrees of accuracy depending on the specific problem to be addressed, the time frame at disposition and the expertise available. These various levels of accuracy are covered by proposing the use of ( a ) simulations, ( b ) indicators whose values are directly related to increases in expected restoration intervention costs and reductions in service, and ( c ) the percentage of fulfilment of indicators. Once resilience has been estimated, the methodology provides guidance on how to set resilience targets with or without cost–benefit analysis. For demonstration, the explanation of the steps of the guideline is supported by their use for a simple transport system.